SEJARAH HUTAN SEBAGAI PENDIDIKAN MITIGASI BENCANA - Basuki Wibowo; Muhammad Syaifulloh (Universitas Muria Kudus, 2022)
The purpose of this study is to determine the history of the forest and its potential as a learning material for disaster mitigation education.The research method uses a qualitative approach. The research time was in June–September 2021 on the grounds that it coincided with the cycle of people cultivating agricultural land. Sources of research data consisted of key informants, namely elders and community leaders of the Dayak Gado and documents in the form of letters, archives both regional and national, as well as documentation (photos) and recordings. Researchers made observations in several forests and conducted Focus Group Discussions (FGD) with traditional leaders, school principals and several Dayak community assistance institutions. The validation technique uses triangulation techniques from traditional institutions, community leaders (elders), and the Village Government. While the analysis technique uses the flow developed by Miles Huberman, namely the interactive flow which includes data collection, data reduction, data presentation and verification/getting conclusions.The results show that the existence of forests in West Kalimantan is a former village or field of the Dayak community which has one of the functions of plant and animal conservation. Forests, in this case tembawang in the Dayak community, can prevent hydrological disasters such as floods. Environmental history of forests can be used as learning materials for disaster mitigation education. Implementation in history subjects in schools requires 3 pillars, namely teachers, learning strategies and supporting aspects. Teachers are very important in an effort to give students understanding about the knowledge of forest history as disaster mitigation education. The success of disaster mitigation education lies in the ability of teachers to master environmental history and provide students with an understanding of the importance of awareness of tradition and history, awareness of position and awareness of action in students.